Adsorption of pentachlorophenol by various modified oil palm empty fruit bunch biochars - Nalaya, Puvaneswaree (2019)
The past application of pentachlorophenol (PCP) as a pesticide and wood preservative caused wastewater contamination in Malaysia. The PCP is highly toxic and resistant to biodegradation, hence, adsorption is one of the efficient methods for its remediation. Recently, physical and chemical modifications of biochars have drawn great attention because they can enhance the surface area, porosity and functional groups of the biochars, thus increase the adsorption capacity and provide other environmental benefits. There is no reported study on the application of physically and chemically modified oil palm empty fruit bunch biochar (EFBB) as a sorbent for PCP removal from wastewater. Therefore, the present study determines the effects of different particle sizes (<0.5 mm and <2.0 mm), chemical modifications (HCl, NaOH and FeCl3), solution pHs (3, 5 and 7) and pyrolysis temperatures (350, 550 and 650 oC) on the adsorption capacities of EFBB for PCP. The adsorbents were analyzed for their ash content, Brunauer- Emmett-Teller (BET) surface area, pore volume, iodine number, surface morphology, functional groups, pH, electrical conductivity, cation exchange capacity, CHNSO and their molar ratios, elemental composition, oxygen surface acidic groups and zeta potential. The adsorption of PCP by the adsorbents was conducted using the different concentrations of PCP (0 – 500 mg L-1). The sorption isotherm data were fitted to the Freundlich and Langmuir adsorption isotherms. The first study was carried out to determine the effects of different particle sizes (<0.5 mm and <2.0 mm) of EFBB in adsorbing PCP as compared to activated carbon (AC). The PCP sorption isotherm to the biochars was best described by the Freundlich model with higher sorption rates observed for the <0.5 mm EFBB compared to the <2.0 mm EFBB. However, the commercial AC had the highest adsorption capacity compared to the <0.5 mm and <2.0 mm EFBBs. The second study was initiated to determine the effects of different chemical modifications (HCl, NaOH and FeCl3) of EFBB in adsorbing PCP as compared to the unmodified EFBB and the AC. The adsorption isotherm of PCP by all the adsorbents was better fitted the Freundlich compared to the Langmuir model. Results showed higher adsorption capacity (KF) of the chemically modified EFBBs than the unmodified EFBB. The modified EFBBs also had a higher BET surface area, aromaticity and surface functional groups and these properties increased the adsorption capacities of the modified EFBBs for PCP. However, the commercial AC had the highest KF value among all the modified and unmodified EFBBs. A study was conducted to determine the effects of pHs (3, 5 and 7) on the sorption capacity of the <2.0 mm EFBB. The Freundlich model can fit the sorption data well (R2 > 0.9319) and the adsorption capacity decreased as the solution pH increased from 3 to 7. This is because PCP exists as an anionic species at pH 5 to 7 while it exists as a neutral species at pH 3 to 5, thus reduces the PCP sorption with an increase in the solution pH from 3 to 7. Another study was performed to determine the adsorption of PCP by biochars produced at different temperatures (350, 550 and 650 oC) as compared to the AC. The Freundlich model best fit the PCP adsorption onto the 350 oC EFBB while no PCP adsorption occurs onto the EFBB produced at 550 oC and 650 oC. The 350 oC EFBB showed a high adsorption capacity due to its high porosity and more oxygenated functional groups. However, the AC showed the highest adsorption capacity. The commercial AC had the highest adsorption capacity compared to all the EFBBs due to its highest BET surface area and micropore volume. These findings recommended that the EFBB with small particle size (<0.5 mm), pyrolyzed at a low temperature (350 oC) and activated with NaOH had the potential for alternative adsorbents of PCP removal from wastewater considering the high cost of commercial AC.